If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9k = 6(-2k + 12) Reorder the terms: -9k = 6(12 + -2k) -9k = (12 * 6 + -2k * 6) -9k = (72 + -12k) Solving -9k = 72 + -12k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '12k' to each side of the equation. -9k + 12k = 72 + -12k + 12k Combine like terms: -9k + 12k = 3k 3k = 72 + -12k + 12k Combine like terms: -12k + 12k = 0 3k = 72 + 0 3k = 72 Divide each side by '3'. k = 24 Simplifying k = 24
| 176=8X^2-42x | | 5x+-43=9x+25 | | 400+50w=1.200 | | 6(10v-15)=5(-14+14v) | | 7u=-10+6u | | 6(-9j-18)=-20j-2(18j+4) | | 7(-1+4x)=77 | | 11j=-6j-15 | | 2x+8+4x=20 | | 6(-9j-18)=-20j-2(18+4) | | -5(y+1)=5 | | 6(-9j-18)=20j-2(18+4) | | 5(8-4x)=-100 | | -3(-16z+20)-19z=20z-6 | | -8+6x=3x-5 | | 3(1)-2(-2+7)=-7 | | -15w-9.65=-8.6w+3.4w+9.95 | | y=0+60x | | y=150+35x | | -14.7f=0.24-12.3f | | 288+9y=18 | | -2(5x-10)=70 | | -12x+2y=-4x+10 | | X^2=13x+220 | | -15.45-11.7q=-11.1q-4.05 | | -2(n-2)+4=64 | | 36x+3=5 | | (9x^2)-(x)+9=0 | | 10*3y-2=4y-y+8 | | 16.2-3.8g=-11.9g | | 7(5-x)=42 | | 6b^2+45b=0 |